Relationship of cardiorespiratory fitness with screen time and physical activity in adolescents - Aisha Shakeel; Syeda Ghulam Fatima Sughra Zaidi; Muhammad Imran Zaib; Syed Nazir Abbas Naqvi; Zara Khalid; Zubaria Binte Tanveer (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the correlation of cardio-respiratory fitness with screen time and physical activity in healthy adolescents. Methods: An analytical cross sectional study was conducted in various schools of Rawalpindi and Islamabad from February 2019 till July 2019. Ethical approval was obtained by the ethical review committee of Foundation University Islamabad and higher authorities of school settings and written informed consent was obtained from all the participants. Non probability convenience sampling was done on N= 250 adolescents of ages 11-17 years including both genders. Participants were selected on the basis of inclusion and exclusion criteria. Cardiorespiratory fitness was evaluated through YMCA 3 min Step test, physical activity levels using physical activity questionnaire for adolescents (PAQ-A) and screen time via HELENA screen time Questionnaire. Data was entered and analysed on SPSS v.21. Quantitative variables were expressed as mean ± SD and Spearman’s Rank Correlation Test was applied to determine correlation between variables. Results: 250 adolescents were recruited in our study. Gender wise distribution comprised of 128 (51.2%) males and 122 (48.8%) females. Age ranged from 11-17 years with mean age of 14.24 ± 2.177 years. The result shows that there is no significant correlation between cardiorespiratory fitness and physical activity (r=0.09, p=0.15) and between cardiorespiratory fitness and screen time in adolescents (r=-0.12, p=0.58). Continuous...